Spectrum of SLC20A2, PDGFRB, PDGFB, and XPR1 mutations in a large cohort of patients with primary familial brain calcification. Issue 4 (15th January 2019) - Guo, Xin‐Xin; Zou, Xiao‐Huan; Wang, Chong; Yao, Xiang‐Ping; Su, Hui‐Zhen; Lai, Lu‐Lu; Chen, Hai‐Ting; Lai, Jing‐Hui; Liu, Yao‐Bin; Chen, Dong‐Ping; Deng, Yu‐Chun; Lin, Pan; et al.
Abstract: Primary familial brain calcification (PFBC) is a rare neurodegenerative disorder with four causative genes ( SLC20A2, PDGFRB, PDGFB, and XPR1 ) that have been identified. Here, we aim to describe the mutational spectrum of four causative genes in a series of 226 unrelated Chinese PFBC patients. Mutations in four causative genes were detected in 16.8% (38/226) of PFBC patients. SLC20A2 mutations accounted for 14.2% (32/226) of all patients. Mutations in the other three genes were relatively rare, accounting for 0.9% (2/226) of all patients, respectively. Clinically, 44.8% of genetically confirmed patients (probands and relatives) were considered symptomatic. The most frequent symptoms were chronic headache, followed by movement disorders and vertigo. Moreover, the total calcification score was significantly higher in the symptomatic group compared to the asymptomatic group. Functionally, we observed impaired phosphate transport induced by seven novel missense mutations in SLC20A2 and two novel mutations in XPR1 . The mutation p.D164Y in XPR1 might result in low protein expression through an enhanced proteasome pathway. In conclusion, our study further confirms that mutations in SLC20A2 are the major cause of PFBC and provides additional evidence for the crucial roles of phosphate transport impairment in the pathogenies of PFBC. Abstract : We made a genetic diagnosis in 16.8% of PFBC probands and identified 30 mutations; Mutations in SLC20A2 are the major cause of PFBC, while the other three genes are relatively rare; Our findings also strongly support crucial roles of phosphate transport impairment in the pathogenies of PFBC.